Improving Social Science Learning Ability Using Demonstration Methods for Grade VI Students of Public Elementary School 014 Rambah Hilir - Suparji Suparji (Indonesian Journal of Basic Education, 2023)
Demonstration Method is a way of demonstrating objects or tools used by teachers in teaching and learning activities with the aim of making it easier for students to receive teaching materials or subject matter. The better the method, the more effective the attainment of the goal, because it requires a benchmark that comes from several factors to determine the intended goal. This method can improve the social science learning abilities of Grade VI students at SD Negeri 014 Rambah downstream, with this method children are interested in learning, and creativity emerges in learning. With this method the authors still consider the time, the circumstances of the children, and the problems identified before conducting classroom action research, so that they are right in taking action. There is evidence of an increase from cycle I to cycle II of successful learning. This method is carried out by identifying problems, formulating problems and carrying out actions and evaluating. So that with this method can improve student achievement